Effect of Vancomycin Applied to the Surgical Site on Fracture Healing in a Diabetic Rat Model. (March 2023) - Hernandez, Alexis; Rahman, Ohidur; Kadkoy, Yazan; Lauritsen, Katherine L.; Sanchez, Alexandra; Innella, Kevin; Lin, Anthony; Lopez, Jonathan; O'Connor, J. Patrick; Benevenia, Joseph; Paglia, David N.; Lin, Sheldon S.; et al.
Background: Prophylactic vancomycin treatment decreases the prevalence of surgical site and deep infections by >70% in diabetic patients undergoing reconstructive foot and ankle surgery. Thus, determining whether clinically relevant local vancomycin doses affect diabetic fracture healing is of medical interest. We hypothesized that application of vancomycin powder to the fracture site during surgery would not affect healing outcomes, but continuous exposure of vancomycin would inhibit differentiation of osteoblast precursor cells and their osteogenic activity in vitro. Methods: The vancomycin dose used to treat the diabetic rats was a modest increase to routine surgical site vancomycin application of 1 to 2 g for a 70-kg adult (21 mg/kg). After femur fracture in BB-Wistar type 1 diabetic rats, powdered vancomycin (25 mg/kg) was administered to the fracture site. Bone marrow and periosteal cells isolated from diabetic bones were cultured and treated with increasing levels of vancomycin (0, 5, 50, 500, or 5000 µg/mL). Results: Radiographic scoring, micro–computed tomography (µCT) analysis, and torsion mechanical testing failed to identify any statistical difference between the vancomycin-treated and the untreated fractured femurs 6 weeks postfracture. Low to moderate levels of vancomycin treatment (5 and 50 µg/mL) did not impair cell viability, osteoblast differentiation, or calcium deposition in either the periosteum or bone marrow–derived cell cultures. In contrast, high doses of vancomycin (5000 µg/mL) did impair viability, differentiation, and calcium deposition. Clinical Relevance: In this diabetic rodent fracture model, vancomycin powder application at clinically relevant doses did not affect fracture healing or osteogenesis.